2003
DOI: 10.1037/0022-006x.71.2.399
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between aggressive attributional style and violence by psychiatric patients.

Abstract: The authors propose a new theoretical construct for understanding the risk of violent behavior by psychiatric patients: the aggressive attributional style. They propose that a cognitive style characterized by external hostile attributions increases the risk of violence by mentally ill persons. To evaluate this hypothesis, they administered several self-report measures relevant to the aggressive cognitive style, as well as measures of violent behavior in the community, to 110 psychiatric inpatients. Higher scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
66
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 22 publications
(23 reference statements)
7
66
1
Order By: Relevance
“…In this study, as expected, the overall disturbance in mental state as measured by the BPRS total was predictive of violence, although correlations (Table 4) with the frequency of violent behaviour were small and non-significant. The agitation -excitement subscale and in particular the hostility-suspiciousness subscale were the strongest predictors, and this is consistent with previous research (Gray et al, 2003;Lowenstein et al, 1990), and this adds further support to the aggressive attributional style link with violence (McNiel et al, 2003a). The finding that hostile and suspicious symptoms are predictive of violence in this study supports the findings of epidemiological studies demonstrating the association between Threat/ Control Override symptoms (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, as expected, the overall disturbance in mental state as measured by the BPRS total was predictive of violence, although correlations (Table 4) with the frequency of violent behaviour were small and non-significant. The agitation -excitement subscale and in particular the hostility-suspiciousness subscale were the strongest predictors, and this is consistent with previous research (Gray et al, 2003;Lowenstein et al, 1990), and this adds further support to the aggressive attributional style link with violence (McNiel et al, 2003a). The finding that hostile and suspicious symptoms are predictive of violence in this study supports the findings of epidemiological studies demonstrating the association between Threat/ Control Override symptoms (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Research has already identified effective cognitive orientated interventions for anger problems that may reduce the risk of violence (Chemtob, Novaco, Hamada, & Gross, 1997;Novaco and Renwick, 1998;Haddock, Lowens, Brosnan, Barrowclough, & Novaco, 2004). The findings in this study also support the attributional style theory of violence (McNiel et al, 2003a). Enhancing the anger regulatory items of the NAS should be a target of therapeutic interventions, although further well designed treatment trials are required to confirm this.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…McNeil, Eisner and Binder (2003) recently developed a measure specifically to assess the ''aggressive'' cognitive style in 110 psychiatric inpatients. This included attributions about the hostile intent of others, beliefs regarding the perception of threat, and also beliefs about the appropriateness of physical violence.…”
Section: Attributional Biasmentioning
confidence: 99%
“…physical, verbal, anger, hostility). Other studies have shown links between attributional style and violent behavior (physical aggression or threats with a weapon; McNiel, Eisner, & Binder, 2003) and physical or relational aggression (Bailey & Ostrov, 2008). These studies in combination show further evidence for social-cognitive mechanisms producing higher levels of aggression in various forms.…”
Section: Chapter 4 Discussionmentioning
confidence: 68%